2014
DOI: 10.1089/jpm.2014.0085
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Advance Care Planning for Patients with Metastatic Cancer: A Pilot Quality Improvement Initiative

Abstract: Outpatient ACP is feasible early in the care of patients with stage IV cancer through systematic improvement in workflow and motivated providers. Education and infrastructure were pivotal to routine development of advance care plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…Substitute decision‐maker is a trusted individual named by the patient (Zhou et al, 2010). Different names were used, like power of attorney for health care (Hu et al, 2010; Obel et al, 2014; Zhou et al, 2010), healthcare proxy (Thomas et al, 2019; Zhou et al, 2010) or healthcare surrogate (Bickel et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Substitute decision‐maker is a trusted individual named by the patient (Zhou et al, 2010). Different names were used, like power of attorney for health care (Hu et al, 2010; Obel et al, 2014; Zhou et al, 2010), healthcare proxy (Thomas et al, 2019; Zhou et al, 2010) or healthcare surrogate (Bickel et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Obel and colleagues 16 at the Kellogg Cancer Center showed that outpatient acp discussions were feasible in patients with recently diagnosed stage iv lung cancer. Improvement in workflow and involvement of motivated providers were key elements that resulted in almost 70% of patients having notes about advance directives in their medical record.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…As a quality improvement initiative at NorthShore, Obel et al created and implemented an ACP navigator in the electronic health record (EHR; EPIC, Verona, Wisconsin), coupled with tools (including an ACP guidebook and educational video) to facilitate these discussions, small group training sessions on how to conduct ACP given by palliative care providers, and nursing support to aid efficient delivery and completion of ACP. 9 All cardiologists and oncologists at NorthShore were trained in the use of these tools and the ACP navigator and were strongly encouraged to incorporate these novel workflow changes into their daily practices.…”
Section: Introductionmentioning
confidence: 99%